DAYA GUNA LIVE PROBIOTIC DIBANDINGKAN HEAT-KILLED PROBIOTIC UNTUK TERAPI DIARE AKUT PADA BALITA - , Atik Indriyani, dr ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diarrhea remain one of the most causes of morbidity and mortality in children in developing countries. Probiotic is now well known give beneficial effect to decrease frequency of diarrhea and shorten diarrhea duration. There are two kinds of probiotic, namely live probiotic and heat-killed probiotic. The aim of this study was to compare effectivity of live and heat-killed probiotic in children aged 6-60 months with acute diarrhea in decreasing duration, frequency of diarrhea and weight gain. This was a randomized controlled trial single blind study to children aged 6-60 months with diagnosis acute diarrhea enrolled and divided in two groups. One group received live probiotic and other hand heat-killed probiotic. The diarrheal duration, frequencies of diarrhea and weight gain were noted. All children received standard treatment of diarrhea and had probiotic as adjuvant treatment. T-test was used in this study. There were 165 children (64,2 % boys and 358 % girsl) with acute diarrhea who meet the inclusion and exclusion criteria were enrolled in this study, divided in two groups